Faktor Risiko Kejadian Stunting pada Balita Umur 12-36 Bulan Periode 1 April S/D 30 April 2022: Studi Kasus di Puskesmas Sorendiweri Kabupaten Supiori - Gerda Gerda; Nur Gilang; Asih Prasetyowati (STIKES HAKLI Semarang, 2023)
Stunting in toddlers is an indicator of the nutritional state of the community. Stunting is a condition where the child's height according to age (TB/U) is below minus two standard deviations (<-2SD) and can increase mortality and morbidity. Stunting can lead to decreased cognitive, motor, and language development, short stature, increased risk for obesity and its comorbidities, and decreased reproductive health. The purpose of the study was to find out the risk factors and most at risk for stunting incidence in toddlers aged 12-36 months. This type of research is quantitative analytical with a case-control study design. Sampling was carried out by Total Sampling, namely 78 toddlers in the case group and 78 toddlers in the control group. The bound variable is the incidence of stunting while the independent variable is exclusive breastfeeding, birth weight of toddlers, mother's education level, mother's job, and family economic status. Data were obtained through observation and interviews with questionnaires. The child's height is measured using a microtoise. Univariate analysis was carried out, bivariate analysis using Chi-Square by looking at Odds Ratio (OR), p value and X2 and multivariate analysis using multiple logistics analysis. The results of the bivariate analysis showed that the risk factor for stunting in toddlers was the birth weight of the toddler (X2Count=41.134; p=0.000; OR=13,257; 95%CI=4,673-20,298), maternal education level (X2Count=49,937; p=0,000; OR=13,257; 95%CI=1,275-4,615). The results of the univariate analysis showed that the high-risk variable was the mother's education level (p = 0.000; exp(B)=18,495). Therefore, it was concluded that the risk factors for stunting incidence in toddlers aged 12-36 months in the work area of the Sorendiweri Health Center, Supiori Regency are 9.7 times the risk of low birth weight, the level of education of the mother at risk of 13.2 times and the work of the mother at risk of 2.4 times.